Neurointerview as the latest method of marketing research - V. M. Nikonorov; D. V. Miroshnichenko; A. V. Nikiforova (Вестник университета)
The modern marketing paradigm requires not only data collection, but also a deeper understanding of the emotional component of consumer behavior. An innovative approach to marketing research such as neurointerview has been presented. This approach combines traditional in terviewing methods with advanced computer vision technologies. It al lows to identify and analyze emotional reactions of study participants in real time. Neurointerview provides a unique opportunity to study consumer preferences, as well as their emotional reactions to specific products, services, and marketing messages. During the survey, participants fill out a standard questionnaire, and their facial expressions are recorded by the camera. Emotional reactions can be analyzed in real time, and a dynamic profile of consumer emotions can be compiled. Neurointerview results turn into a journal that records the percentage of subjects showing various emotions, such as joy, surprise, and excitement. This data allows marketers to gain a deeper understanding of consumer behavior and emotional preferences, opening up new opportunities to develop more accurate and effective marketing strategies and products. The results provide precise forecasts of market trends.